Pengaruh Penganggaran Berbasis Kinerja Terhadap Kenaikan Tunjangan Kinerja Bawaslu Dalam Perspektif Hukum Keuangan Negara - Naufal Rizqiyanto; Annisa Al Rahman (Jurnal Interpretasi Hukum, 2024)
This research explores the impact of performance-based budgeting on the increase in the performance allowance of Indonesia's Election Supervisory Agency (Bawaslu) from the perspective of state financial law. This research examines how performance-based budgeting, which emphasises efficiency, effectiveness, and accountability, affects financial management and justifies the increase in allowances. By analysing the legal framework, empirical data, and performance metrics, this study aims to provide a comprehensive understanding of the alignment between budget allocations and performance outcomes in Bawaslu. The method used is normative research with primary, secondary and tertiary legal materials. The data generated from legal materials are described to find objective results. The results of this study The use of a performance-based budgeting system (ABK) by Bawaslu has influenced the policy of increasing performance allowances. Bawaslu's performance measurement refers to the principles of state finance, including efficiency, economic effectiveness, accountability, responsibility, professionalism, proportionality, and openness. The increase in Bawaslu's performance allowance is in accordance with the performance improvement that has been evaluated by Menpan RB, which is the institution responsible for bureaucratic reform.